2019
DOI: 10.1002/alr.22323
|View full text |Cite
|
Sign up to set email alerts
|

The impact of medical therapy on cognitive dysfunction in chronic rhinosinusitis

Abstract: Background: Cognitive dysfunction in chronic rhinosinusitis (CRS) is o en overlooked despite potentially broad implications. Earlier work has demonstrated decreased cognitive function in CRS patients at baseline. In this study we sought to prospectively evaluate the impact of initial, appropriate medical therapy on subjective and objective cognitive function, fatigue, and workplace productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 50 publications
0
28
1
1
Order By: Relevance
“…Additionally, CRS patients had worse simple reaction time scores compared to controls on computerized neurocognitive testing, a difference that persisted regardless of polyp status. Since this initial report, several studies have found improvements in patient‐reported and objective cognitive function after both medical and surgical treatment of CRS 75–77 …”
Section: General Concepts Of Rhinosinusitismentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, CRS patients had worse simple reaction time scores compared to controls on computerized neurocognitive testing, a difference that persisted regardless of polyp status. Since this initial report, several studies have found improvements in patient‐reported and objective cognitive function after both medical and surgical treatment of CRS 75–77 …”
Section: General Concepts Of Rhinosinusitismentioning
confidence: 98%
“…A case‐control study found that patients with CRS report significantly worse scores on the Cognitive Failures Questionnaire as compared with controls 74 . Several subsequent studies have found improvements in patient‐reported and objective cognitive function after both medical and surgical treatment of CRS 75–77 …”
Section: Introductionmentioning
confidence: 99%
“…The current review encompassed 4 studies utilizing the FSS in patients with CRS, with a mean of 4.2, suggesting problematic fatigue for this subgroup. Taken together, these subjective parameters are suggestive of poor sleep; however, it is also possible that other disease factors, such as the patient's heightened inflammatory state, 33 sinonasal‐specific symptoms, or altered cognition, 2,43 may be responsible for changes in sleep‐related PROMs, independent of one's actual sleep quality. Evidently, the mechanisms in which these diseases may lead to sleep dysfunction are complex and likely multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study in the US reported that appropriate medical therapy improved several measures of cognitive dysfunction in patients with CRS. [ 25 ] In addition, in a multicenter study, patients with CRS with nasal polyps reported significant improvements in cognitive scores after endoscopic sinus surgery. [ 26 ] The declines in inflammation and cytokines following medical treatment or surgery may be 1 factor driving improvements in cognition.…”
Section: Discussionmentioning
confidence: 99%